GAMBARAN TINGKAT KEPADATAN HUNIAN KAMAR DAN INSIDEN PENYAKIT YANG DIDERITA WARGA DI BANJAR LINGKUNGAN BADAK SARI TAHUN 2022 - Eka Luthfiana Irjayanti; Mochammad Choirul Hadi; I Made Bulda Mahayana (Poltekkes Kemenkes Denpasar, 2022)
Residential density is one of the trigger indicators of high rates of disease transmission. The density of room occupancy in one residential house will have an influence on its residents. The area of the room that is not proportional to the number of occupants will cause Over Crowded. The purpose of this study is to find out the level of room occupancy density and the incidence of diseases suffered by residents of Banjar Lingkungan Badak Sari in 2022. The type of research used in this study is descriptive research. Data collection is carried out by observation, interview, and measurement of the physical quality of the environment and knowing the picture of the level of room occupancy density and the incidence of infectious diseases suffered by residents of Banjar Lingkungan Badak Sari. From the results of data collection obtained that from 74 samples there were 36,5% or 27 rooms that have a high density while 63,5% or 47 rooms have been qualified. The disease suffered by residents during the last 3 months that suffered the most is fever with a percentage of 29,7% or 22 people who suffer from fever. The conclusion of the results about the level of room occupancy in The Banjar Lingkungan Badak Sari in 2022 is categorized as quite good. The advice that can be given to researchers can then use this research as a reference in conducting follow-up research and it is very expected that the next researcher can further explore the problems that will be the material for the research.